Quantum Bio-Informatics II: From Quantum Information to Bio-Informatics - Accardi, L; Freudenberg, W; Ohya, M (Quantum bio-informatics II : from quantum information to bio-informatics : Tokyo University of Science, Japan, 12-16 March 2008, 2009)
The purpose of this proceedings volume is to look for interdisciplinary bridges in mathematics, physics, information and life sciences, in particular, research for new paradigms for information and life sciences on the basis of quantum theory. The main areas in this volume are all related to one of the following subjects: (1) mathematical foundation of quantum mechanics, (2) quantum information, (3) quantum algorithm and computation, (4) quantum communication, (5) white noise analysis and quantum dynamics, (6) chaos dynamics and adaptive dynamics, (7) experimental studies of quantum computer, (8) bio-informatics and (9) genome analysis.